The Use of Meaningful Instruction Design (Mid) Learning Model to Improve Student Learning Outcomes in Force and Motion Science Subject Materials - Irma Sari Daulay; Sutan Botung Hasibuan; Sahnilawati Nasution (Al-Aulad: Journal of Islamic Primary Education, 2023)
The aims of this study were (1) to find out how the application of the Meaningful Intruction Design (MID) learning model in improving student learning outcomes in the natural sciences subject matter of style and motion in class IV SD Negeri 1404 Batang Sosa, Ulu Sosa District. The type of research used is classroom action research (PTK) which consists of two cycles. The data collection technique was carried out by observation, documentation and tests with 25 students as subjects, 10 boys and 15 girls. The results of the study obtained were i.e. students i2 i(8%) categorized as good, i17 i(68%) i was not very good and i6 i(24%) i was very bad. In cycle II, the test results of the i25 students who are in that class have the i grades that students get only i1 person i(4%) icategory is very good, i10 person i(40%) is categorized as good, i10 person i(40%) is category is not very good iand i4 ipeople i(16%) ivery bad category. In cycle III, the results of the test were i25 students, i9 students (36%) were in the very good category, i13 students (52%) were categorized as good, and i3 students (12%) were in the poor category. So it can be concluded that applying the MID learning model can improve the learning outcomes of class IV students at SD Negeri 1404 Batang Sosa.